Creative Visual Arts to Improve Life Quality of Autistic Children in Chiang Mai Orphanage Houses - Suriyong, Eakaphong (Journal of Graduate MCU KhonKaen Campus, 2022)
This research aimed to study the result of creative visual arts for improving the quality of life of children with autism in the Chiang Mai Nursing Home. This study’s population and sample group were 20 autistic children from Baan Samarn Jai Foundation, Chiang Mai Province. The questionnaire was analyzed by percentage, mean and standard deviation to compare the changes in the sample before and after participating in the activities. Organizing learning through creative visual arts activities to improve the quality of life of children with autism in nursing homes in Chiang Mai found that, after participating in creative visual arts activities, 75.00% of the sample had better physical behavior, 80.00% had better cognitive and emotional behavior, and 78.00% had better social behavior.